JWTAMH: JSON Web Tokens Based Authentication Mechanism for HADOOP. - Gupta, Manish; Gupta, Anish; Raj S., Britto; Sharma, Annu (EAI Endorsed Transactions on Scalable Information Systems, 2024)
The Hadoop platform has become a widely adopted distributed computing platform for handling large-scale data processing tasks. However, the security of the Hadoop platform has become a major concern due to the increased risk of cyber-attacks. To address this concern, various security mechanisms have been proposed for the Hadoop platform, including authentication and access control. This research paper proposes a token-based authentication mechanism to enhance the security of the Hadoop platform. The proposed mechanism utilizes a combination of Kerberos and JSON Web Tokens (JWT) for secure communication between Hadoop components. The experimental results demonstrate the effectiveness of the Single point of failure, Guessing attack, Replay Attack, Brute force attack, and Dictionary attack. The proposed model has better performance in terms of average processing time and accuracy of authentication than other models.
Keywords: Hadoop; Token-based Authentication; Kerberos; JWT; Security; Access Control